Design of a scalable framework for lunar habitats - Irawan, Jonathan; De Kestelier, Xavier; Ozruh, Levent; Cullen, David C.; Solly, James; Angelaki, Evgenia Makrina (International Astronautical Federation (IAF), 2025)
The last decade has signalled the crystallisation of a common, global agenda to revisit mankind's exploration and habitation of the moon. Government agencies and private companies are presenting a common front to deliver critical missions and programs such as the Lunar gateway, working towards a permanent presence on the lunar surface. As an outcome of ESA's Open Space Innovation Program, our paper presents a scalable, holistic design and architectural framework for long term human habitation on the Moon, embedding key solutions for environmental protection and mitigation, construction methodology and assembly of a scalable architecture, life support and an overall mission architecture. Our approach differs from existing lunar concepts (i.e. static masterplans that predefine settlement layouts), devising a system that enables continual reconfiguration in response to future, unpredictable social societal needs, technological and operational advancements. The novelty of the proposal will focus around the reconfigurability, reusability, and accommodation of various growth scenarios of a lunar base. This design principle extends to the proposal's approach to system engineering, life support, modular construction techniques, and in-situ resource utilisation which are directly embedded into the architectural framework to ensure seamless expansion. The proposal is led through a human centric, design-based approach, prioritising long term self- sufficiency, sustainability, and well-being of future lunar settlements. Formulation of solutions accommodate for a constantly evolving programmatic brief, taking into consideration the physiological, psychological, and social needs of a wider inhabitant demographic. The system is comprised out of several interdependent architectural components; an ISRU-based modular construction system for radiation protection, tensairity-based, pressure-retaining inflatable modules for habitation, a modular interior fit-out system, and hard-shell modules for vertical circulation. The system thus exists as a "kit-of-parts", serving as a comprehensive atlas of architectural elements and life support systems for further testing and development, with any advancements feeding back into its central design principles. Design reviews involving participation of multidisciplinary industry experts and partners were held several times throughout the design development of the project, ensuring robust scientific basis for design concepts and strategies.
Keywords: architecture; scalable; habitat; reconfigurability; design; kit-of-parts